Enrichment of bakery products with biogenic minerals - Олішевський, Валентин Вікторович (Technology audit and production reserves, 2015)
The paper presents the study of the mineral composition of bakery products balance, production of biogenic minerals. A method of production of biogenic metals Mg and Mn colloids suspensions during electric sparkle dispersion in water has been presented. Physicochemical properties of received colloids suspensions have been defined. The possibility of integrated colloid suspensions of biogenic metals Mg and Mn for use in the baking industry has been studied. It is proved that the use of suspensions of colloids of biogenic metals Mg and Mn has reduced the duration of proofing dough pieces, improved crumb color of finished products and extended duration of stale. Also, along with the organoleptic and physicochemical indicators mineral content of bakery products has been improved, which enables directional regulation of the chemical composition of finished products.